(3YedjGJ GdHfhc habG dbGfhf GdJLGQI GdYeGfj (B(55 (3dSfI (B1990) /s - (3GdebOGOi, YGOd Ydis ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2006)
(3jYQV gPG GdcJGH eGjdj GdebOeI(B-(3GdaUd GdChd (B: (3hOjYI GdfbhO (B: (3GdeHMK GdChd (B: (3eaghe hOjYI GdfbhO hNUGFUgG hCfhGYgG (B: (3GdeHMK GdKGfj (B: (3BKGQ YbO hOjYI GdfbhO(B-(3GdaUd GdKGfj (B: (3hOjYI GdChQGb GdeGdjI (B: (3GdeHMK GdChd (B: (3eaghe hOjYI GdChQGb GdeGdjI hCfhGYgG (B: (3GdeHMK GdKGfj BKGQ YbO hOjYI GdChQGb GdeGdjI(B-(3GdaUd GdKGdK (B: (3EjLGQ GdNRGFf (B: (3GdeHMK GdChd (B: (3eaghe EjLGQ GdNRGFf hWHjYJg GdbGfhfjI (B: (3GdeHMK GdKGfj (B: (3BKGQ YbO EjLGQ GdNRGFf(B-(3GdaUd GdQGHY (B: (3Gdfbd GdeUQaj (B((3GdJMhjd GdMSGHj(B) : (3GdeHMK GdChd (B: (3eaghe Gdfbd GdeUQaj hTQhWg hMGdGJg (B: (3GdeHMK GdKGfj (B: (3GdWHjYI GdbGfhfjI ddfbd GdeUQaj (B: (3GdeHMK GdKGdK (B: (3BKGQ Gdfbd GdeUQaj (B: (3GdeHMK GdQGHY (B: (3BKGQ GdMLR hGdEadGS(B-(3GdaUd GdNGeS (B: (3GdGYJeGOGJ GdeUQajI (B: (3GdeHMK GdChd (B: (3aJM GdGYJeGO (B((3GdGYJeGO GdHSjW(B) : (3GdeHMK GdKGfj (B: (3GdGYJeGO GdeSJfOj(B-(3GdaUd GdSGOS (B: (3GdNUe (B: (3GdeHMK GdChd (B: (3eaghe GdNUe hTQhWg (B: (3GdeHMK GdKGfj (B: (3GdWHjYI GdbGfhfjI ddNUe (B: (3GdeHMK GdKGdK (B: (3BKGQ GdNUe(B-(3GdaUd GdSGHY (B: (3NWGH GdVeGf (B: (3GdeHMK GdChd (B: (3TQhW NWGH GdVeGf (B: (3GdeHMK GdKGfj (B: (3GdWHjYI GdbGfhfjI dNWGH GdVeGf (B: (3GdeHMK GdKGdK (B: (3BKGQ NWGH GdVeGf(B-(3GdaUd GdKGef (B: (3GdMSGH GdLGQj (B: (3GdeHMK GdChd (B: (3eaghe GdMSGH GdLGQj hUhQg (B: (3GdeHMK GdKGfj (B: (3TQhW GdeOahYGJ hfWGb GdMSGH GdLGQj (B: (3GdeHMK GdKGdK (B: (3BKGQ GdMSGH GdLGQj (B: (3GdeHMK GdQGHY (B: (3Zdb GdMSGH GdLGQj hCKQ GdEadGS Ydjgs
(3HjHdjhZQGajG U(B.283s
Keywords: (3GGdGYJeGOGJ GdeUQajIs; (3GdYedjGJ GdHfhcs; (3GdbGfhf GdJLGQjs; (3Gdfbd GdeUQajs; (3GdhOjYIs